Workplace Stressors of Deaf and Hearing Workers - Beha, Admira; Čajlaković Kurtalić, Sanela; Petrović, Amila (Technium Social Sciences Journal, 2022)
The occurrence of stress in the workplace is frequent and present in all areas of work. Population deaf workers are at some risk when it comes to the impact of stress in the workplace. The research aims is to determine factors that directly cause stress in the working environment deaf and hearing workers. The sample consisted of 30 deaf workers and 33 hearing workers. For the needs of the research, the measuring instrument of the International labor organizations was used (2003). Research results show that isolated stressors factors are more common in a subsample of deaf subjects. Fear of losing a job, fatigue and short deadlines, lack of support from colleagues and managers, constant change of obligations, feeling insecurities, fear of position in the firm, and communication difficulties are isolated causes of stress in deaf workers. Workflow errors are associated with a feeling of fear and insecurity, they appear due to their insufficient information due to communication difficulties.